2009
DOI: 10.1080/07420520903044331
|View full text |Cite
|
Sign up to set email alerts
|

Timing Light Treatment for Eastward and Westward Travel Preparation

Abstract: Jet lag degrades performance and operational readiness of recently deployed military personnel and other travelers. The objective of the studies reported here was to determine, using a narrow bandwidth light tower (500 nm), the optimum timing of light treatment to hasten adaptive circadian phase advance and delay. Three counterbalanced treatment order, repeated measures studies were conducted to compare melatonin suppression and phase shift across multiple light treatment timings. In Experiment 1, 14 normal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…In experimental studies, light-at-night suppresses melatonin in a dose-response manner; however, even low intensities of light exposure (100 lux) are able to both suppress and phase shift the human melatonin rhythm (8). Not only intensity, but also timing of light exposure is important for the direction of the aMT6s phase shift, as described by the phase-response curve (45,46). We not only examined the phase shifting abilities of light exposures occurring during the night shift, but also tested the time period immediately after the shift and up to initiation of sleep and results were similar when morning light was taken into account.…”
Section: <0001mentioning
confidence: 99%
“…In experimental studies, light-at-night suppresses melatonin in a dose-response manner; however, even low intensities of light exposure (100 lux) are able to both suppress and phase shift the human melatonin rhythm (8). Not only intensity, but also timing of light exposure is important for the direction of the aMT6s phase shift, as described by the phase-response curve (45,46). We not only examined the phase shifting abilities of light exposures occurring during the night shift, but also tested the time period immediately after the shift and up to initiation of sleep and results were similar when morning light was taken into account.…”
Section: <0001mentioning
confidence: 99%
“…Furthermore, even though individual light exposure measures were not included in this study, our previous studies in these hospitals have shown that night lighting is quite dim at 40 to 50 lux (43,50), which is much lower than experimental conditions. Because intensity and timing of light exposures can impact melatonin patterns (51)(52)(53), individual light assessment should be incorporated in future studies. Finally, the modeling of time-series data by cosinor analysis did not take into account serial correlation of observations within participants, which may violate the assumption of homoscedasticity of error terms.…”
Section: Cancer Epidemiol Biomarkers Prev; 25(5) May 2016mentioning
confidence: 99%
“…The 3 mg SR melatonin was ingested at times based on established melatonin PRCs for optimum phase advance Lewy et al 1998;Revell and Eastman 2005). When morning light treatment was administered without melatonin the previous afternoon, its timing was based on established light PRCs (Khalsa et al 2003;Paul et al 2009;Revell and Eastman 2005). When morning light treatment was given after melatonin treatment the previous afternoon, we anticipated up to an hour advance of circadian phase due to the afternoon melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both exogenous melatonin and light treatment can shift circadian rhythms forward or backward according to phaseresponse curves (PRC) which define the optimum treatment times for phase advance and phase delay (Lewy et al 1998;Paul et al 2009;Revell and Eastman 2005).…”
Section: Introductionmentioning
confidence: 99%